Epithelial arginase-1 is a key mediator of age-associated delayed healing in vaginal injury - Wilkinson, Holly N.; Reubinoff, Benjamin; Shveiky, David; Hardman, Matthew J.; Menachem-Zidon, Ofra Ben (Frontiers in Endocrinology, 2022)
Pelvic organ prolapse is a disorder that substantially affects the quality of life of millions of women worldwide. The greatest risk factors for prolapse are increased parity and older age, with the largest group requiring surgical intervention being post-menopausal women over 65. Due to ineffective healing in the elderly, prolapse recurrence rates following surgery remain high. Therefore, there is an urgent need to elucidate the cellular and molecular drivers of poor healing in pelvic floor dysfunction to allow effective management and even prevention. Recent studies have uncovered the importance of Arginase 1 for modulating effective healing in the skin. We thus employed novel in vitro and in vivo vaginal injury models to determine the specific role of Arginase 1 in age-related vaginal repair. Here we show, for the first time, that aged rat vaginal wounds have reduced Arginase 1 expression and delayed healing. Moreover, direct inhibition of Arginase 1 in human vaginal epithelial cells also led to delayed scratch-wound closure. By contrast, activation of Arginase 1 significantly accelerated healing in aged vaginal wounds in vivo, to rates comparable to those in young animals. Collectively, these findings reveal a new and important role for Arginase 1 in mediating effective vaginal repair. Targeting age-related Arginase 1 deficiency is a potential viable therapeutic strategy to promote vaginal healing and reduce recurrence rate after surgical repair of pelvic organ prolapse.